COMPUTERIZED SYSTEM RESERVATION & PURCHASE THE BOOK AT THE GRAMEDIA BOOK SHOP - Tri Busono; Rafael A. Gafar, Ir (Jurnal Sistem Informasi, 1998)
Analysis of computerized reservation systems and the purchase of books at Gramedia Bookstore, where previous work has many constraints. We applied this system Process of making mail order (PO) to become more effective and efficient. Supply of goods to be more selective, thus avoiding inventory pile up. Scheduling receipt of goods become more regular. Recording / data collection more accurate inventory, so it is easy to make analysis and forecasting. Data recording more organized and sorted so that it will facilitate the search process again. The process of making / presenting the report the receipt of goods becomes more rapid and complete. And procedures for revenue collection would be better.